A systematic literature review on DevOps capabilities and areas - Teixeira, D.; Pereira, R.; Henriques, T.; Faustino, J.; Silva, M. (International Journal of Human Capital and Information Technology Professionals, 2020)
Businesses today need to respond to customer needs at an unprecedented speed. Driven by this need for speed, many companies are rushing to the DevOps movement. DevOps, the combination of Development and Operations, is a new way of thinking in the software engineering domain that recently received much attention. Since DevOps has recently been introduced as a new term and novel concept, no common understanding of what it means has yet been achieved. Therefore, the definitions of DevOps often are only partly relevant to the concept. This research presents a systematic literature review to identify the determining factors contributing to the implementation of DevOps, including the main capabilities and areas with which it evolves.